MEMAHAMI TUGAS PERKEMBANGAN ANAK USIA DINI - Ananda Rachmaniar; Realudin Ainun Zanzabil (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
The background to this community service is parents' low knowledge of the developmental tasks children need to achieve at an early age and their low understanding of how to provide stimulus to young children late in achieving their developmental tasks. The method used is the PAR (Participatory Action Research) method, which consists of the preparation, implementation, and closing stages. The results obtained are that parents and posyandu cadres gain knowledge about the characteristics of early childhood, early childhood development tasks, and the importance of this developmental task being carried out well, parents and posyandu cadres understand better how to provide stimulus and also apply parenting patterns to early childhood, as well as creating better communication relationships and parenting patterns in dealing with early childhood.